2006
DOI: 10.1001/jama.296.14.1731
|View full text |Cite
|
Sign up to set email alerts
|

Translation of Research Evidence From Animals to Humans

Abstract: Smoking was an exclusion criterion for controls, whereas 4 of the 21 cases were regular smokers of 2 to 10 cigarettes per day. Mean urinary excretion rates of 8-iso-PGF 2␣ were similar in the 4 smokers (404 pg/mg of creatinine) and in the 21 cases considered as a whole (482 pg/mg of creatinine). Urine albumin excretion rates were not tested. There was only a small glucose variability between each day (day 1 mean amplitude of glycemic excursions [MAGE], 74 mg/ dL; day 2 MAGE, 76 mg/dL), and MAGE values on day 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
469
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 614 publications
(477 citation statements)
references
References 4 publications
6
469
0
2
Order By: Relevance
“…However, few of these human trials have shown success (4)(5)(6)(7). The success rate is even worse for those trials in the field of inflammation, a condition present in many human diseases.…”
mentioning
confidence: 99%
“…However, few of these human trials have shown success (4)(5)(6)(7). The success rate is even worse for those trials in the field of inflammation, a condition present in many human diseases.…”
mentioning
confidence: 99%
“…[18][19][20][21][22] This problem has been highlighted by a number of recent, high-profile commentaries from the pharmaceutical industry, 18,19,23 funding agencies, including the National Institutes of Health, 24,25 scientific journals, 26,27 veterinarians, 28 academics, and biostatisticians. [29][30][31][32][33][34][35][36] This is of particular importance when animal models are used to advance the development of clinical therapeutics. Not only does this level of uncertainty potentially waste millions of funding dollars, 37 but there are also genuine ethical concerns regarding the clinical evaluation of agents with supporting rationale that is solely on the basis of experimental evidence derived from studies in animal models.…”
Section: Common Concerns About Preclinical Study Design and Reportingmentioning
confidence: 99%
“…This has limited the translation of the target to the clinic [4]. Screening systems using different species, such as worm, fruit fly, and zebrafish, have proven extremely useful for basic science insights and, on occasion, repurposing previously approved drugs from the Food and Drug…”
Section: Limitations With Current Cns Modelsmentioning
confidence: 99%
“…Equally important, these models should enable the investigation of genetic and environmental risk factors contributing to diseases in a rapid and economical way. Currently used models often do not reflect a typical human response [2][3][4], despite efforts underway to better characterize these models and increase their preclinical value in predicting safety and efficacy in the clinic [5,6]. Therefore, there is a great need to develop disease-and patient-specific models from cells directly affected in CNS disorders.…”
mentioning
confidence: 99%